Sedition Act 1948: a legal study on the relevancy of the act / Mohd Hafiz Ramlee and Muhammad Ihsan Norkhair - Ramlee, Mohd Hafiz; Norkhair, Muhammad Ihsan (Faculty of Law, 2016)
Sedition Act 1948 was adopted by the British rulers from existing 19th Century legislation from colonial India into the then Malaya before independence. Its purpose was to combat threats from Communists insurgency.1 The Sedition Act originated as an Enactment (Enactment 13/1939), then as an Ordinance (Ordinance 14/1948) and later amended and passed as the Sedition Act (Act 15/1970), which was enforced on 14th April 1970.2 The act since then has gone through two major amendments. The first amendment introduced provisions relating to the protection of Bumiputera’s special position under the Federal Constitution, the monarchy and the preeminent position of the national language. The second amendment both restricted and expanded the seditious definition by removing seditious acts against the government and judiciary while adding seditious act relating to religion and talks of secession.